TOURISM LOGISTICS MANAGEMENT AFFECTING TOURIST SATISFACTION IN NAKHON NAYOK PROVINCE - Tungjitsommanas, Jirawat; Thoucharee, Sedthapoom; Sangkhasuk, Rataphol; Boonsirichai, Morakot (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
Research topic is Tourism Logistics Management Affecting Tourist Satisfaction in Nakhon Nayok Province. The objectives are to study the level of satisfaction of tourists towards Tourism Logistics and analyze the influence of Tourism Logistics affecting Tourist Satisfaction by collecting data with questionnaires from 400 tourists. The tools used to collect data in this research are questionnaires and interviews after that analyzed by descriptive analysis method by finding the percentage, mean, and standard deviation and the correlation of two independent variables by using the Pearson Product moment correlation Coefficient. The results of the research were as follows: Tourists were satisfied with tourism in Nakhon Nayok Province and the overall of satisfaction of tourism logistics components was at a high level. When considering each aspect, it was found that the overall of the facilities had the highest average of 3.85, followed by the overall information flow with the mean of 3.83. While the overall of the physical flow was the lowest mean average is 3.50. The analysis of Pearson's correlation coefficient statistical analysis, the results of the study found that the relationship between each aspect of tourism logistics management was the physical flow, Information flow and facilities and satisfaction level of tourists. There was a statistically significant correlation with the tourist satisfaction level of 0.05 with correlation coefficients(r) of 0.383, 0.711 and 0.720, respectively.